Empirical and Statistical Study of Elicitation Complications - Arshad, Sidra; Fazal, Hafiza Tahira; Nawaz, Tahir (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
The performance of Requirement Engineering is like framework for software development process. All-inclusive software has four mainstays of requirement engineering processes i.e. Functional and non-functional requirements, design, implementation and testing build the complete software fortification on top of the mainstays. Requirement engineers have to face numerous challenges to develop successful and impressive software. Requirements Engineering (RE) leads software development process. Different constraints and needs of users are explored as well as hitches in previous system are depicted. The scope of this study is to exemplify the difficulties faced by users in the utmost maiden phase of RE Requirements Elicitation and a framework is presented as well. A survey was conducted in different campuses of Universities in Pakistan for this purpose. Questionnaire was distributed among project development students of various disciplines to gather and highlighted the problems during Requirements Elicitation. Finally the predictive statistical software SPSS was used to input the collected data for more precise calculations, the results of which are discussed in section 3.